Bacteremia detected on peripheral blood smear in small animal patients presenting to the Emergency Department and its association with prognosis to discharge - Ford, Summer Scout; Whelan, Megan; Ewing, Patty; Sinnott-Stutzman, Virginia B. (Frontiers in Veterinary Science, 2025)
ObjectiveDetection of bacteremia on peripheral blood smear (PBS) is rare and may be a poor prognostic indicator for small animal patients. This study aimed to determine the relationship between bacteremia on PBS and survival to discharge in clinically ill patients presenting through the Emergency Department (ED).MethodsThis retrospective study analyzed data from two veterinary tertiary care facilities from 2014 to 2024. Records from 16 client-owned animals presenting to the ED with PBS-detected bacteremia were reviewed. The primary outcome was survival to discharge. Secondary outcomes evaluated associations between survival in these patients with glucose level, leukocyte count, toxic change, band neutrophils, total bilirubin, blood pressure, and antibiotic use. Statistical comparisons between categorical data were made using Fisher’s exact test. A p-value of <0.05 was considered significant.ResultsIn-hospital mortality of the 16 patients was 75% (12/16). Hyperglycemia was positively associated with survival (p = 0.0099). All survivors were cats. No other parameters showed statistical significance between survivors and non-survivors.ConclusionPBS-detected bacteremia in clinically ill small animals was associated with a high in-hospital mortality in this study. Further investigation is warranted to better understand its clinical relevance and potential diagnostic utility.